Migration and Diaspora Formation : New Perspectives on a Global History of Christianity. - Burlăcioiu, Ciprian. (Arbeiten Zur Kirchengeschichte Series, 2022)
Arbeiten zur Kirchengeschichte first began publication in 1925 and can claim to be one of the most tradition-rich historical book series. It presents research on the history of Christian churches and dogmas through the ages but also publishes papers on related disciplines such as archeology, history of art and literary studies. One of the series' leading features is its consistent striving to combine historical-methodical precision with systematic contextualization of each examined topic. In recent years the series has increasingly published studies on themes relating to the history of Christian culture and ideas, viewed within a methodically open perspective on the history of Christianity.